ZFAND5 Is an Independent Prognostic Biomarker of Perihilar Cholangiocarcinoma - Liu, Pei; Wang, Yijia; Duan, Lingling (Frontiers in Oncology, 2022)
Background Cholangiocarcinoma (CCA) is a highly aggressive malignancy with extremely poor prognosis. Perihilar CCA (pCCA) is the most common subtype of CCA, but its biomarker study is much more lagged behind other subtypes. ZFAND5 protein can interact with ubiquitinated proteins and promote protein degradation. However, the function of ZFAND5 in cancer progression is rarely investigated, and the role of ZFAND5 in pCCA is never yielded. Materials and Methods In this study, we established a pCCA cohort consisting of 72 patients. The expression of ZFAND5 in pCCAs, and the paired liver tissues, intrahepatic bile duct tissues and common bile ducts (CBD) tissues were detected with IHC. ZFAND5 mRNA in pCCAs and CBDs was detected with qRT-PCR. The pCCA cohort was divided into ZFAND5low and ZFAND5high subsets according to the IHC score. The correlations between ZFAND5 expression and clinicopathological parameters were assessed bychi-square test. The prognostic significance of ZFAND5 expression and clinicopathological parameters was estimated by univariate analysis with Kaplan-Meier method, and by multivariate analysis with Cox-regression model. Results Expression of ZFAND5 in pCCAs was substantially higher than that in interlobular bile ducts and common bile ducts, but lower than that in liver tissues. The ZFAND5low and ZFAND5high subsets accounted for 44.4% and 55.6% of all pCCAs respectively. ZFAND5 high patients had much lower survival rates than the ZFAND5low patients, with the average survival time as 31.2 months and 19.5 months respectively. ZFAND5 was identified as an independent unfavorable prognostic biomarker of pCCA with multivariate analysis. Conclusion ZFAND5 expression was up-regulated in pCCAs compared with the CBDs. We identified ZFAND5 as an independent biomarker of pCCA, which could provide more evidence for the molecular classification of pCCA, and help stratify the high-risk patients based on the molecular features.